The Analysis of the Three Levels of Communication in Mata Najwa Talk Show - Deasy Yunita Siregar (VISION, 2018)
Communication is an important activity in one's life. Whether humans or animals, everyone wants to share feelings, emotions, thought, ideas and hence develops one way or the other to communicate. It is a basic human right and essential to our quality of life as a social species. In everyday day life we come across various forms of communication. We communicate with one another on may different levels, because we do not have direct access to the thoughts and feelings of another people. We must rely on communication to convey messages to another. There is more to communication than simply using language to speak to one another. Communication exists on a number of levels and in a variety of forms.Key words: Communication and messages